2023
DOI: 10.3389/fgene.2023.985764
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-Seq reveals key MicroRNAs involved in fat metabolism of sheep liver

Abstract: There is a genetic difference between Hu sheep (short/fat-tailed sheep) and Tibetan sheep (short/thin-tailed sheep) in tail type, because of fat metabolism. Previous studies have mainly focused directly on sheep tail fat, which is not the main organ of fat metabolism. The function of miRNAs in sheep liver fat metabolism has not been thoroughly elucidated. In this study, miRNA-Seq was used to identify miRNAs in the liver tissue of three Hu sheep (short/fat-tailed sheep) and three Tibetan sheep (short/thin-taile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Their function is to inhibit gene expression by binding to complementary sites in the 3' untranslated region (3'UTR) of target genes, thereby inhibiting protein translation or inducing degradation of the target mRNA (Papaconstantinou et al 2012). Several miRNAs have been identified in the field of adipogenesis, including oar-miR-432 (Fei et al 2023), miR-376a (Chen et al 2020), and miR-378 (Liu et al 2021). In our study, we found that miR-187 could bind to lncIMF1, therefore, we initially conducted independent investigations into the functions of miR-187 and found that miR-187 could inhibited differentiation of intramuscular preadipocytes.…”
Section: Discussionmentioning
confidence: 75%
“…Their function is to inhibit gene expression by binding to complementary sites in the 3' untranslated region (3'UTR) of target genes, thereby inhibiting protein translation or inducing degradation of the target mRNA (Papaconstantinou et al 2012). Several miRNAs have been identified in the field of adipogenesis, including oar-miR-432 (Fei et al 2023), miR-376a (Chen et al 2020), and miR-378 (Liu et al 2021). In our study, we found that miR-187 could bind to lncIMF1, therefore, we initially conducted independent investigations into the functions of miR-187 and found that miR-187 could inhibited differentiation of intramuscular preadipocytes.…”
Section: Discussionmentioning
confidence: 75%